An intelligent decision-making framework for asphalt pavement maintenance using the clustering-PageRank algorithm. Issue 11 (1st November 2020) - Han, Chengjia; Fang, Mingjing; Ma, Tao; Cao, Hongyou; Peng, Hao
Abstract : With ever-increasing road mileages worldwide, more pavement deterioration and ageing present great challenges to the maintenance and rehabilitation (M&R) of road pavement. In this study, an intelligent decision-making framework is developed for pavement maintenance using the clustering-PageRank algorithm (CPRA) based on historical big data. The proposed model is applied to a 3.5 km pavement (500 road sections) and leads to recommendations for the optimal pavement maintenance plans with appropriate possibilities. The results indicate that seven plans are the same as those obtained by the experience-based maintenance approach, while the other three are similar. The framework is also verified by comparison with the experience-based maintenance activities and is found to have limited reliability when dealing with a small quantity of solutions. The method and results of this study are expected to serve as a reference for decision makers to make well-informed project decisions on the optimum M&R activities.